PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN PATH GOAL THEORY TERHADAP KINERJA PENDIDIK DI LEMBAGA PENDIDIKAN ISLAM - Sibawaih, Sibawaih (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, dan Publikasi, 2023)
Organizational culture is now being discussed every where, both among experts and among practitioners and executives because many of these organizational cultures have succeeded in making an organization more stable, more advanced and more anticipative of environmental changes. Organizations have their own culture that characterizes an organization. The method used in this research article is a qualitative method using library research on theories that are relevant to research problems. Meanwhile, the analysis model uses a descriptive analysis model. As a source of information in this article, researchers use several books, journals, articles and other online reading media related to this research. The culture of an organization plays a fairly important role in the organization, because a good culture will be able to provide comfort which then supports the performance of its members. Conversely, an organizational culture that is not good or that is not in accordance with the personalities of its members will trigger a decrease in the performance of each member.